Effects of vaccination and the new neuraminidase inhibitor, laninamivir, on influenza infection. - Takuro Mizuno; Shigeru Mizuno; Tsugiyasu Kanda (PLoS ONE)
Background Evidence of the effectiveness of influenza vaccination in children and elderly adults is limited, although this population has the highest risk for influenza infection. Materials and methods We enrolled 4443 participants, aged 3-97 years, who had influenza-kit-positive results during seasons 2007-12, including 2135 with influenza A, 534 with A/H1N1, and 1643 with influenza B. Eligible subjects completed a questionnaire to identify past influenza infection and vaccination history. For the diagnosis of current influenza infection, subjects were examined, and pharyngeal swabs were collected and tested using the Capilia flu rapid diagnosis kit to confirm influenza infection. An interim analysis was performed using clinician-based surveillance data for the entire four seasons of influenza infection in Japan. Results In 3035 adults aged 14-64 years, administration of the influenza vaccine significantly reduced the frequency of infection (P<0.01) in the 2008 and 2010 seasons, but not in the 2009 and 2011 seasons. Moreover, the vaccine did not reduce the frequency of infection in children (aged <13 years) and older adults (aged >65 years) significantly. Laninamivir, oseltamivir phosphate, zanamivir hydrate, and amantadine hydrochloride were administered to 1381, 2432, 1044, and 100 patients, respectively. They were effective in >97% of patients, with no significant differences being found. Adverse effects were few. However, the recurrence rate of influenza infection after treatment was significantly reduced in patients who received laninamivir compared with that in those who received oseltamivir and zanamivir (P<0.01). The effectiveness of laninamivirdid not decrease. Conclusions The vaccines administered had limited efficacy in reducing the frequency of influenza infection in young adults. Laninamivir significantly reduced the recurrence of influenza infection when compared with other neuraminidase inhibitors.